Interference Cancellation in WCDMA Systems using Tapered Beamformers - Gupta, Meenakshi (My University, 2007)
The field of wireless communications is growing at an explosive rate, covering many technical areas. The deployment of cellular systems is a success and as the subscriber population continues to grow at a rapid pace, service providers may get capacity problems due to limited available frequency spectrum. Consequently, service providers are forced to find methods of enhancing the coverage and the capacity of their cellular networks. A promising future method suggested is to utilize adaptive antennas, which has also been recognized as one potential economic approach. Adaptive base station antennas have been proposed as a means to achieve the requested longer range and higher capacity in cellular systems. In WCDMA, there is large number of interferers present in the system due to frequency reuse factor of one. The large numbers of interferers in these systems require a beamforming technique that would efficiently suppress the power in the undesired direction at the same time maximizing the power in the desired direction. For these systems side lobe adjustment would be a simple solution towards suppressing intercell and intracell interference and hence improving CIR performance rather than placing the nulls in the direction of individual interferers. In this dissertation, a novel two-step tapered beamforming algorithm is analyzed for flexible side lobe adjustment. The algorithm places a very low side lobe level over a large width in the beam pattern. The convergence of this algorithm is fast and requires only two to three iterations. This beamforming algorithm is suitable for uplink and downlink since it is based on the DOAs estimated in uplink. The algorithm provides flexible parameter adjustment (side lobe level, null depth, main lobe width and null width) together with very low computational effort.
Keywords: WCDMA System; Tapered Beamformer; SDMA; Beampattern